PENGARUH FAKTOR – FAKTOR FUNDAMNETAL INTERNAL PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FARMASI PERIODE 2011 – 2015 - Nofazulia Nofazulia (Master of Management, Mataram University, 2017)
The increasing leverage ratio every year can not boost up the share closing price that tends to fluctuate and decrease every year. The fluctuation in the profitability and the growth ratio of company also tend to decrease followed by the decreasing of share price. This research is aimed at determining the effect of debt to equity ratio (DER) and return on equity (ROE), and company growth on the share price in manufacture company in subsector of pharmacy during the period 2011 – 2015.The population of this research is all manufacture company in subsector of pharmacy registered in Indonesian Stock Exchange in 2011 – 2015. The samples were 8 manufacture companies selected through purposive sampling. The data were collected through documentation and analyzed with multiple linear regression using SPSS program.The partially (t-test) research showed that 1) Leverage did not have effect on the share price, 2) profitability had negative effect on the share price, 3) company growth did not have effect on the share price in manufacture companies subsector pharmacy in 2011 – 2015.Keywords: debt to equity ratio (DER), return on equity ratio (ROE), company growth, share price